Economics of Agricultural Supply Chain Design: A Portfolio Selection Approach. (1st October 2016) - Du, Xiaoxue; Lu, Liang; Reardon, Thomas; Zilberman, David
Abstract: Agrifood firms in a globalizing and competitive market, both in developing and developed countries, often undertake innovations in products and technologies. Innovators such as firms and other agents develop supply chains to accommodate the nature of the innovations. In this article we analyze an innovator's supply chain design problem. The design of the supply chain involves three sets of decisions. The first is how much to produce. The second involves how to undertake production, and how many resources to allocate to the production of feedstock (agricultural products that are inputs for processing), processing, and marketing. The third set involves deciding on the amount of feedstock to be obtained through contracts with farmers. We show that the innovator determines its overall level of production by taking advantage of its monopoly power, derived from the innovation in the output market, and behaves as a monopsony in buying feedstock from contractors. These decisions are constrained by the marginal cost of capital and the properties of production and marketing technologies. When the innovator is risk averse, risks in farm production, processing, and marketing will affect both processed output and the share of feedstock bought through contracts.